(untitled) (Research, Society and Development, 2020)
Osteoporosis is the most common osteometabolic disease in the world, although it is more prevalente in the elderly, it affects all age groups and its diagnosis has been increasing in young people due to the longer survival in patients with chronic diseases. This work aims to address the prevention and control of osteoporosis throughout all stages of life. A bibliographical survey was carried out on books, scientific articles and publications issued on the subject by renowned specialized institutions tha made it possible to deepen the theme. It is evidente that the prevention of osteoporosis must occur from the intrauterine period. It is known that childhood and adolescence are the periods when bone mass is most acquired, constituting the main phases to intervene in the prevention of this disease. In adults, it is desired to maintain the acquired boné mass and in the elderly, it is sought to maintain preventive care, carry out early diagnosis and treatment and avoid complications of this disease. It appears that interventions such as adherence to a healthy lifestyle at all ages, with regular physical exercise practices and adequate nutrition, have resulted in effective measures in the prevention of osteoporosis. We conclude the need for a paradigma shift, as osteoporosis is seen as a disease specific to the elderly can be considered late. This work presentes na understanding of osteoporosis from a new perspective, in which we can say that the disease must be prevented at all ages.